Militant democracy and the pre-emptive constitution: from party bans to hardened term limits. Issue 1 (2nd January 2022) - Elkins, Zachary
ABSTRACT: I explore the concept of militant democracy in the context of what appear to be persistent threats to the democratic order. I begin with a reconstruction of the concept with the intention of distinguishing and identifying its historical manifestations. I trace and document two constitutional devices that exhibit the pre-emption and illiberalism that characterizes militant democracy. The first device—party restrictions—is the prototypical example of the concept and is designed to pre-empt extremist intimidation. The second example—hardened term limits—is designed to pre-empt executive ambition. The latter form of bullying may be the most relevant threat, at least in modern Latin America and Africa. In one view, term-limit evasion accelerates a pernicious negative cycle in which constitutional non-compliance begets constitutional weakness, which in turn begets subsequent non-compliance. Such a negative feedback loop is a core problem in law. Militant democracy, the logic of which implies the entrenchment and protection of term limits, could potentially disrupt such negative cycles. The concept could also be useful as an intellectual defense of seemingly non-democratic means of protecting democracy.